Analysis Of Muzakkar And Muannath In Kawniyyat Words: Sura At-takwir - Maryam Binti Mokhtar; Aisyah Humairaa Binti Muhammad Faisal; Tg Ainul Farha Binti Tg Abdul Rahman (USIM Press, 2024)
Volume: 5 No: 2 (page: 13-17)